2016
DOI: 10.1680/jgele.15.00125
|View full text |Cite
|
Sign up to set email alerts
|

Microbially induced calcite precipitation effect on soil thermal conductivity

Abstract: Efficiency of energy piles is strongly affected by soil saturation conditions: low water contents considerably decrease their performance thus limiting the possibility to extend their application to arid environments. This paper investigates the microbially induced calcite precipitation (MICP) technique as a potential means of enhancing the soil–pile heat exchange rates by improving the thermal properties of soil. The study puts the focus on measuring the thermal conductivity of untreated and treaded sand at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Geothermal energy is a clean, renewable, and sustainable energy resource, which has various engineering applications, such as ground source heat pumps (GSHPs) and geothermal energy piles (GEPs) [1]. e performance of such underground energy structures is strongly affected by the saturation degree of soils [2]. It is found that low saturation degree reduced soil thermal conductivity, which lowered the efficiency of heat exchange between soils and the structures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal energy is a clean, renewable, and sustainable energy resource, which has various engineering applications, such as ground source heat pumps (GSHPs) and geothermal energy piles (GEPs) [1]. e performance of such underground energy structures is strongly affected by the saturation degree of soils [2]. It is found that low saturation degree reduced soil thermal conductivity, which lowered the efficiency of heat exchange between soils and the structures [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of small strains, assuming the solid grains incompressible and an isotropic material behavior, we propose a yield function along the lines of Modified Cam Clay, extended to account for an isotropic tensile strength function (e.g. see [34], [46], [41] and [1]), as follows:…”
Section: Plastic Behaviormentioning
confidence: 99%
“…It is worth emphasizing that for If instead, for simplicity, we consider stress-independent elasticity, so that the bulk modulus K is assumed constant (as is also assumed for the shear modulus G ), by exploiting the additive decomposition of strain which leads upon integration to the hardening law ( 5).…”
Section: Appendix B Hardening Lawmentioning
confidence: 99%
See 2 more Smart Citations